2019
DOI: 10.1029/2018gc007941
|View full text |Cite
|
Sign up to set email alerts
|

A Mantle Plume Origin for the Scandinavian Dyke Complex: A “Piercing Point” for 615 Ma Plate Reconstruction of Baltica?

Abstract: The origin of Large Igneous Provinces (LIPs) associated with continental breakup and the reconstruction of continents older than ca. 320 million years (pre-Pangea) are contentious research problems. Here we study the petrology of a 615-590 Ma dolerite dyke complex that intruded rift basins of the magma-rich margin of Baltica and now is exposed in the Scandinavian Caledonides. These dykes are part of the Central Iapetus Magmatic Province (CIMP), a LIP emplaced in Baltica and Laurentia during opening of the Cale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 94 publications
4
58
0
Order By: Relevance
“…The new age for the Corrovarre dolerites as well as similarities in geochemistry (Roberts, ) documents that they are part of the SDC and can be correlated with the rest of the SDC in the southern segment. Tegner et al () have shown that, like the NALIP, the SDC was triggered by elevated upper mantle temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The new age for the Corrovarre dolerites as well as similarities in geochemistry (Roberts, ) documents that they are part of the SDC and can be correlated with the rest of the SDC in the southern segment. Tegner et al () have shown that, like the NALIP, the SDC was triggered by elevated upper mantle temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Suggested paleogeographic reconstruction of Baltica and Laurentia at approximately 620 Ma, based on Tegner et al, . Red stars show the locations of LRD and ED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The break-up of Pannotia from c. 615 Ma onwards occurred as Laurentia, Gondwana and Baltica rifted from each other to form the Iapetus Ocean (Tegner et al 2019 and references therein). The ocean widened until the Late Cambrian, and then started to close following the initiation of eastdipping subduction zones (present reference frame) close to the margin of Laurentia (Cocks & Torsvik 2006).…”
Section: Caledonidesmentioning
confidence: 99%